Women And Catcalling: An Analysis of Contributing Factors and Mitigating of Verbal/Non-Verbal Communication - Lubis, Muhammad Alridho; Rahmayanty, Dinny (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2024)
Sexual harassment in the form of catcalling is prevalent. This research aims to delve into the factors that contribute to catcalling behavior towards women and develop strategies to minimize its occurrence. Employing a literature review methodology, the study gathers information and data from relevant sources pertaining to the issue. Unlike previous research that solely focused on catcalling forms, this study analyzes contributing factors and mitigation strategies. The findings reveal that catcalling manifests in various forms of verbal and non-verbal communication, including whistling, calling, teasing, touching, and, in the most extreme cases, following, insulting, and assaulting the victim. Analysis of contributing factors highlights the pervasive role of patriarchal culture in society, which places power in the hands of men and objectifies women. Additionally, perpetrators of catcalling are driven by a range of psychological factors, such as attraction, a sense of power over women, self-gratification, and a desire for amusement with friends. Efforts to minimize verbal and non-verbal communication in catcalling, stemming from the understanding that catcalling is a form of sexual harassment, include ignoring the perpetrator and pretending to be preoccupied. While silence can be an alternative, resistance from the victim is more effective.